2018
DOI: 10.3390/su10010249
|View full text |Cite
|
Sign up to set email alerts
|

At Home with Sustainability: From Green Default Rules to Sustainable Consumption

Abstract: Abstract:Although it is often assumed that default rules affect change without awareness, this paper suggests that contrast with the default and transition into conscious adoption of the default design may be the starting point to establish long-term changes in consumer behavior. Despite the rooting of default rules in subconscious decision-making, this research finds that, ultimately, awareness drives the demand necessary for the creation of sustainable consumption. Whereas direct appeal to individuals has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Secondly, the analysis carried out suggests that the factor called resource consumption (RESO-COMPS) has a positive and significant effect, although to a lesser extent, on their productivity (RES-PROD-DMC), which would validate Hypothesis 3. This result agrees with that stated by Hale [12] and Mont and Plepys [11], in the sense that an efficient use of resources will tend to increase resource productivity and allow reducing resource scarcity risk, with the consequent lower environmental impact. In the same way, it was observed that public and private investment in research and development, present in the factor in a relevant way with the variables Intramural R&D expenditure (GERD)-Government and Intramural R&D expenditure (GERD)-Business, allows us to face the uncertainty behind climate change in a manner consistent with sustainable economic growth, supporting the rapid technological change necessary as indicated by Baker and Solak [42].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Secondly, the analysis carried out suggests that the factor called resource consumption (RESO-COMPS) has a positive and significant effect, although to a lesser extent, on their productivity (RES-PROD-DMC), which would validate Hypothesis 3. This result agrees with that stated by Hale [12] and Mont and Plepys [11], in the sense that an efficient use of resources will tend to increase resource productivity and allow reducing resource scarcity risk, with the consequent lower environmental impact. In the same way, it was observed that public and private investment in research and development, present in the factor in a relevant way with the variables Intramural R&D expenditure (GERD)-Government and Intramural R&D expenditure (GERD)-Business, allows us to face the uncertainty behind climate change in a manner consistent with sustainable economic growth, supporting the rapid technological change necessary as indicated by Baker and Solak [42].…”
Section: Discussionsupporting
confidence: 92%
“…Mont and Plepys [11] suggested that government intervention was required to change the present framework in order to encourage producers to seek business opportunities based on less resource-intensive product-service offers. Hale [12] showed consumers´environmental awareness as the main driver to create sustainable consumption and pointed out the need to strengthen policies related to this issue.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…be good. 141 The recognition of the power of the standard options influences the way cell phones are configured, the option for health plans, automatic revocation of subscriptions and even environmental preservation, 142 based on the idea of green by default or sustainable 143 by default. 144 The second principle is the presumption of human fallibility itself.…”
Section: The Architecture Of Choices Libertarian Paternalism and Self-composition By Defaultmentioning
confidence: 99%